2016
DOI: 10.1111/dme.13263
|View full text |Cite
|
Sign up to set email alerts
|

Risk of diabetic retinopathy at first screen in children at 12 and 13 years of age

Abstract: AimsTo investigate the relationships between age at diagnosis of diabetes, age at diabetic eye screening and severity of diabetic retinopathy at first and subsequent screenings in children aged 12 or 13 years.MethodsData were extracted from four English screening programmes and from the Scottish, Welsh and Northern Irish programmes on all children with diabetes invited for their first and subsequent screening episodes from the age of 12 years. Retinopathy levels at first and subsequent screens, time from diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 14 publications
0
16
0
1
Order By: Relevance
“…The current population eligible for DR screening in the UK includes all persons diagnosed with diabetes (type 1 or type 2) aged 12 years and over [203]. In the UK, the recommendation is to commence photographic screening in diabetic patients from the age of 12, and this is supported by a large study that reviewed data from 2125 children, aged 12 to 13 years at first screening, recruited from all four UK Nations (England, Scotland, Wales and Northern Ireland) [204]. The study identified that in children diagnosed with diabetes under the age of 2 years, 20.1% had signs of any retinopathy, compared with 6.3% of those diagnosed at the age of 10 years.…”
Section: Section 7: Diabetic Retinopathy In Children and Young Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current population eligible for DR screening in the UK includes all persons diagnosed with diabetes (type 1 or type 2) aged 12 years and over [203]. In the UK, the recommendation is to commence photographic screening in diabetic patients from the age of 12, and this is supported by a large study that reviewed data from 2125 children, aged 12 to 13 years at first screening, recruited from all four UK Nations (England, Scotland, Wales and Northern Ireland) [204]. The study identified that in children diagnosed with diabetes under the age of 2 years, 20.1% had signs of any retinopathy, compared with 6.3% of those diagnosed at the age of 10 years.…”
Section: Section 7: Diabetic Retinopathy In Children and Young Adultsmentioning
confidence: 99%
“…However, only three children (0.14%) were identified as having referable DR at their first screening. Follow-up data was available for 1703 children, with 25 children (1.5%) graded as having referable retinopathy, with only three of whom (0.17%) graded as having PDR [204]. The median time from baseline screening to sightthreatening DR was 3.1 years [204].…”
Section: Section 7: Diabetic Retinopathy In Children and Young Adultsmentioning
confidence: 99%
“…Evidence from the Wisconsin Epidemiologic Study of Diabetic Retinopathy showed a surge in incidence of DR following 5 years into the course of T1DM, supporting DR screening to be commenced within 5 years of diagnosis 58. Alternatively, screening during or shortly after puberty is also acceptable as it is uncommon for patients with T1DM below the age of 12 years to develop DR 59 60. Pregnancy can worsen the severity of pre-existing diabetes which can bring about an earlier onset of DR 61.…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom, a national screening program was introduced from 2002 with the initial age of screening starting at 12 years because there were no reports of vision‐threatening retinopathy before this age . Recently, reported results of 2125 adolescents screened at age 12 to 13 years found referral retinopathy rates of less than 20%, but of these, three individuals with short duration (<5 years) required fast track referral for moderate to severe retinopathy.…”
Section: Introductionmentioning
confidence: 99%